Computational approaches to parallel transmission MRI - Mirfin, Christopher (2020)
This thesis is concerned with the design of spatially-selective RF pulses accelerated by parallel transmission. These pulses perturb the magnetisation in an object within a 2D or 3D sub-volume, whilst leaving magnetisation outside of these regions unaffected. As such, they are shown to be useful in certain dynamic field-shimming strategies.